Satisfaction and self-confidence of nursing students as participants and observers in realistic simulations - Ariane Teixeira; Juliana Petri Tavares; Ana Luísa Petersen Cogo (Universidade Federal do Rio Grande do Sul, 2022)
ABSTRACT Objective: To analyze the satisfaction and self-confidence of Nursing students regarding the learning process, in the roles of participants and observers, in realistic simulation scenarios. Method: Observational study with 44 nursing college students in the south of Brazil. Data collection occurred from September to November 2018, through the application of the Learning Satisfaction and Self-Confidence Scale to realistic simulation scenarios. Data were analyzed using descriptive statistics and generalized estimating equations complemented by Bonferroni. Results: The level of satisfaction was 4.78 (±0.35) and self-confidence in learning was 4.46 (±0.39). Students in the 8th and 9th semesters had the highest means of self-confidence factor (p<0.001) when compared to the others. Conclusion: It was concluded that there was no statistically significant difference in the satisfaction and self-confidence in learning of nursing students with different roles in the simulation scenario.